ACEH'S OLD MOSQUES: RECONCILING OLD AND NEW ARCHITECTURE - Aji Sofiana Putri; Muhammad Naufal Fadhil (Center for Research and Development of Religious Literature and Heritage, 2023)
The growth of congregation activities in Aceh's old mosques has contributed to the area expansion of the old mosques. This article examines three case studies of old mosques in Aceh that represent three scenarios of spatial expansion, including: mihrab extension integrated into the old mosque, side expansion attached to the old building, and expansion by adding a new mosque building. Three old mosques under study were Teungku Di Anjong Mosque in Banda Aceh, the Asal Penampaan Mosque in Gayo Lues, and the Gunong Kleng Mosque in West Aceh. This paper aims to analyze the mosque's spatial connection from three architectural aspects: (1) Pattern of Additional Area, (2) Functionality and Other Features, (3) The Architectural Forms and Materiality of the old and new mosques. A qualitative study was employed through the analysis of architectural and visual images of the three mosques. The study found that adding new spaces to the three mosques significantly divides old and new mosques. The main function of the mosque as a place of worship intertwines with its function as a center of cultural activities as found in the old and new spaces. Furthermore, the old mosque architecture influenced modern mosques, although not completely. The old form harmonized with new materials to reconcile with contemporary construction methods.